2019
DOI: 10.1128/aac.02244-18
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone and Cefotaxime Have Similar Effects on the Intestinal Microbiota in Human Volunteers Treated by Standard-Dose Regimens

Abstract: Ceftriaxone has a higher biliary elimination than cefotaxime (40% versus 10%), which may result in a more pronounced impact on the intestinal microbiota. We performed a monocenter, randomized open-label clinical trial in 22 healthy volunteers treated by intravenous ceftriaxone (1 g/24 h) or cefotaxime (1 g/8 h) for 3 days. We collected fecal samples for phenotypic analyses, 16S rRNA gene profiling, and measurement of the antibiotic concentration and compared the groups for the evolution of microbial counts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 33 publications
9
58
0
Order By: Relevance
“…The results also showed that Bacteroides abundance was not significantly altered by cephalosporin. It supports previous findings investigating the effect of cephalosporins on the intestinal microbiota (Burdet et al 2019;Rashid et al 2015). Apart from a decrease in the abundance of several genera, there was an increase in Christensenella, Rothia, Abiotrophia, Acinetobacter, Anaerotruncus, Holdemania, and Turicibacter.…”
Section: Discussionsupporting
confidence: 91%
“…The results also showed that Bacteroides abundance was not significantly altered by cephalosporin. It supports previous findings investigating the effect of cephalosporins on the intestinal microbiota (Burdet et al 2019;Rashid et al 2015). Apart from a decrease in the abundance of several genera, there was an increase in Christensenella, Rothia, Abiotrophia, Acinetobacter, Anaerotruncus, Holdemania, and Turicibacter.…”
Section: Discussionsupporting
confidence: 91%
“…The research data revealed that CEO, but not CFT, had the ability to enhance the intestinal microbial richness and diversity in colitis mice, which was generally negatively associated with the severity of intestinal‐related diseases . Similarly, Burdet et al pointed out that both ceftriaxone and cefotaxime exhibited a profound reduction on bacterial diversity (Shannon index and number of OUTs) in humans. Antibiotic therapy also reduced the diversity of fecal microbiota in children with ulcerative colitis .…”
Section: Discussionmentioning
confidence: 97%
“…This explains the discrepancies between studies on antibiotic effects. For example, in their study Grohs et al found ecological benefits of substitution from ceftriaxone to cefotaxime [11], while a recent study in healthy volunteers showed no difference between the two third-generation cephalosporins [86]. This difference between the results can be explained by methodological considerations.…”
Section: Biases In the Interpretation Of Studies On The Ecological Immentioning
confidence: 91%